2014
DOI: 10.1111/cmi.12258
|View full text |Cite
|
Sign up to set email alerts
|

Icm/Dot-dependent inhibition of phagocyte migration byLegionellais antagonized by a translocated Ran GTPase activator

Abstract: SummaryThe environmental bacterium Legionella pneumophila causes a severe pneumonia termed Legionnaires' disease. L. pneumophila employs a conserved mechanism to replicate within a specific vacuole in macrophages or protozoa such as the social soil amoeba Dictyostelium discoideum. Pathogen-host interactions depend on the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 65 publications
(88 reference statements)
3
72
0
Order By: Relevance
“…Realtime single-cell tracking of L. pneumophila-infected phagocytes revealed that the velocity and directionality of the cells were decreased, and cell motility as well as microtubule dynamics were impaired. 71 The above results are in agreement with the notion that LegG1 stimulates cell migration by antagonizing (unknown) Icm/Dot-translocated effectors inhibiting cell migration. L. pneumophila might benefit from the LegG1-dependent promotion of cell migration by counteracting Icm/Dot substrates, which destabilize microtubules and thus damage a number of essential cellular pathways such as phagocytosis, vesicle trafficking, cytokinesis and migration.…”
Section: The Ran Activator Legg1 Promotes Pathogen Vacuole Motility Asupporting
confidence: 89%
See 2 more Smart Citations
“…Realtime single-cell tracking of L. pneumophila-infected phagocytes revealed that the velocity and directionality of the cells were decreased, and cell motility as well as microtubule dynamics were impaired. 71 The above results are in agreement with the notion that LegG1 stimulates cell migration by antagonizing (unknown) Icm/Dot-translocated effectors inhibiting cell migration. L. pneumophila might benefit from the LegG1-dependent promotion of cell migration by counteracting Icm/Dot substrates, which destabilize microtubules and thus damage a number of essential cellular pathways such as phagocytosis, vesicle trafficking, cytokinesis and migration.…”
Section: The Ran Activator Legg1 Promotes Pathogen Vacuole Motility Asupporting
confidence: 89%
“…52 Using real-time confocal laser scanning microscopy, we analyzed the dynamics of LCV transport along microtubules in D. discoideum producing either calnexin-GFP 66 or GFP-a-tubulin. 71 Under these conditions, LCVs harboring wild-type L. pneumophila were very motile and rapidly moved along microtubules. In contrast, LCVs harboring DlegG1 mutant bacteria were stalled, and the phenotype was complemented by plasmid-encoded LegG1.…”
Section: The Ran Activator Legg1 Promotes Pathogen Vacuole Motility Amentioning
confidence: 99%
See 1 more Smart Citation
“…For L. pneumophila, more than 300 Icm/Dot substrates are known to date (21)(22)(23). A number of these effectors have been mechanistically characterized and subvert components of the endocytic, retrograde, or secretory vesicle-trafficking machinery, including small GTPases of the Arf and Rab (21,(24)(25)(26), as well as the Ran (27,28) families; the vacuolar H ϩ -ATPase (29); the autophagy machinery (30); the retromer complex (31); and phosphoinositide (PI) lipids (32,33).…”
mentioning
confidence: 99%
“…LegG1 has sequence homology to the Ran GEF RCC1. Although purified LegG1 does not have direct Ran GEF activity in vitro, it induces Ran activation in infection, thus promoting LCV recruitment of the RanGTP-binding protein RanBP1, stabilization of microtubules, LCV motility, and phagocyte migration (Rothmeier et al 2013;Simon et al 2014). The advantages of keeping the LCV mobile are not fully understood; however, it might enable the LCV to leave the default "track" of phagosomes, which would otherwise efficiently ensure the encounter and fusion with endocytic vesicles.…”
Section: Sustained Movement Of the Lcv Inside The Cell: Keep Moving Omentioning
confidence: 99%